Memahami Komunikasi Beda Budaya Antara Suku Batak Toba dengan Suku Jawa di Kota Semarang - Simbolon, Debora (Jurnal The Messenger, 2012)
The development of increasing open world on various aspects of human life which is supported by the mobility and movement and exchange of information quickly. The information of exchage is quickly explain the fact that all human beings can not circumvent intercultural communication.The results of this study explains the theory and science of communication theory explain Phenomenology by Maurice Marleu-Ponty (Littlejohn 1999) is the assumption informants from the experiences and try to understand every event in their environment with personal experiences.The research method used is descriptive qualitative analysis, it is a process of focusing attention on the simplification and transformation of the raw data that comes from the written notes in the field, the presentation of the data is done by using a form of narrative text, drawing conclusions and verification.Different cultural communication barriers conflict for communicators. Language and ethnosentrism be one of the triggers of conflict, such as Batak s language that is considered rude to make Javanise misunderstand the message. Solutions to communication barriers that are of mutual respect and learn from each other, for example Javanise learning Batak s langguage and Bataknese learning Javanese s langguage.Bottom of Form